Paired Double Consciousness: A Du Boisian Approach to Gender and Transnational Double Consciousness in Thai Kathoey Self-Formation. (12th April 2021) - Lynne, Alyssa
Abstract: Sociologists have not adequately explored how Du Bois' concept of double consciousness could be used to study the role of cisnormative oppression in self-formation or how it could enrich studies of self-formation beyond the Atlantic world. This article addresses these gaps by merging postcolonial feminist theory and the concept of double consciousness to analyze kathoey self-formation . Kathoey are gender nonconforming (GNC) individuals in Thailand who are assigned male at birth and live as women. Drawing upon participant observation, in-depth interviews, and content analysis, I propose an extension to double consciousness called "paired double consciousness." This framework explains how cisnormative and neocolonial oppression lead kathoey to experience two veils. The first veil divides self-formation between kathoey and dominant cisgender worlds within Thai society, which produces "gender double consciousness." The second veil divides self-formation between kathoey and dominant transgender worlds within a global community, which creates "transnational double consciousness."